Performance of Thermal Insulation Covering Materials to Reduce Postharvest Losses in Okra - Jutarat Rattanakaran; Rattapon Saengrayap; Nattapol Aunsri; Sirada Padee; Chureerat Prahsarn; Hiroaki Kitazawa; Chris F. H. Bishop; Saowapa Chaiwong (Horticulturae, 2021)
The efficiency of different thermal insulation covers in minimizing temperature fluctuations in cool chain management was investigated to reduce postharvest loss and maintain okra quality during storage and transportation. The four thermal insulation covering materials: (1) heat reflective sheet with thin nonwoven (HRS + TNNW), (2) heat reflective sheet with thick nonwoven (HRS + TKNW), (3) metalized Tyvek® (MTyvek) and (4) metalized foam sheet (MFS) were studied and compared with perforated linear low-density polyethylene (P-LLDPE) as the typical handing package for okra distribution alongside no covering as the control. The material properties, transpiration rate, vital heat, temperature profiles (air and pulp temperatures), relative humidity, mass loss and incidence of decay were determined throughout a simulated supply chain. Results exhibited that HRS + TNNW and HRS + TKNW covers had the lowest thermal heat energy (Qx) and moderate R-value. These two covers maintained low temperature fluctuation with the lowest rate of air and pulp temperature changes, reflecting in lowest mass loss and decay in okra. The HRS + TNNW cover yielded less decay (1%) in okra, compared to commercial covers; MTyvek (16%) and MFS (9%). Results showed that HRS + TNNW exhibited great potential as a thermal insulation cover to reduce postharvest loss in okra (5%) compared to typical handling (11–18%) and could be considered as alternative material to reduce the use of foam sheets in cool chain management distribution packaging of okra under ambient environment conditions.